2021
DOI: 10.1101/2021.11.29.21267041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Variant Detection with a High-Fidelity CRISPR-Cas12 Enzyme

Abstract: Laboratory tests for the accurate and rapid identification of SARS-CoV-2 variants have the potential to guide the treatment of COVID-19 patients and inform infection control and public health surveillance efforts. Here we present the development and validation of a COVID-19 variant DETECTR® assay incorporating loop-mediated isothermal amplification (LAMP) followed by CRISPR-Cas12 based identification of single nucleotide polymorphism (SNP) mutations in the SARS-CoV-2 spike (S) gene. This assay targets the L452… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In the current version of CriSNPr, six of the widely used CRISPR diagnostic platforms have been included due to enough literature support for their design guidelines. The field of CRISPRDx being rapidly evolving, several other Cas proteins have been recently reported for detecting pathogenic DNA or RNA and their associated variants (66,67). As more and more literature supporting these diagnostic pipelines become available, we would include them in the server.…”
Section: Discussionmentioning
confidence: 99%
“…In the current version of CriSNPr, six of the widely used CRISPR diagnostic platforms have been included due to enough literature support for their design guidelines. The field of CRISPRDx being rapidly evolving, several other Cas proteins have been recently reported for detecting pathogenic DNA or RNA and their associated variants (66,67). As more and more literature supporting these diagnostic pipelines become available, we would include them in the server.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports of CRISPR detection of SNPs in the literature. In particular, Cas12a, 10,13 Cas13a, 7,9,11,12,14 and Cas14a 15 have been used to confirm that CRISPR-based assays are sufficiently specific for SNP detection. For example, Shan et al 14 showed differences in initial reaction velocities for Cas13 when activated by WT versus SNPs within six bases of the target 5′ end but did not consider the effects of SNPs on Michaelis−Menten kinetics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There have been several reports of CRISPR detection of SNPs in the literature. In particular, Cas12a, 10,13 Cas13a, 7,9,11,12,14 and Cas14a 15 have been used to confirm that CRISPR-based assays are sufficiently specific for SNP detection. For example, Shan et al .…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports of CRISPR detection of SNPs in the literature. In particular, Cas12a, 10,13 Cas13a, 7,9,11,12,14 and Cas14a 15 have been used to confirm that CRISPRbased assays are sufficiently specific for SNP detection. For example, Shan et al 14 showed differences in initial reaction velocities for Cas13 when activated by WT versus SNPs within 6 bases of the target 5' end but did not consider effects of SNPs on Michaelis-Menten kinetics.…”
Section: Introductionmentioning
confidence: 99%